1966
DOI: 10.1099/00221287-43-1-31
|View full text |Cite
|
Sign up to set email alerts
|

Effert Of Lactoperoxidase and Thiocyanate on the Growth of Streptococcus pyogenes and Streptococcus agalactiae in a Chemically Defined Culture Medium

Abstract: SUMMARYA chemically defined culture medium was used to study the effect of purified lactoperoxidase and thiocyanate on the growth of several cultures of Streptococcus pyogenes and S. agalactiae. While not inhibited by either component alone, S. pyogenes growth was completely inhibited when both components were present in the medium. The growth inhibition was annulled completely by glutathione, thioglycollic (mercaptoacetic) acid or catalase. S. pyogenes glyceraldehyde phosphate dehydrogenase was inhibited by l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

1969
1969
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 7 publications
(2 reference statements)
0
30
0
Order By: Relevance
“…In contrast to the large number of studies of the effects of the LPO and related systems on S. mutans, there have been relatively few studies of the effect on S. sanguinis (formally sanguis) (Carlsson, 1980;Carlsson et al, 1983;Courtois et al, 1995;van der Hoeven & Camp, 1993), and we are not aware of any efforts to quantify the effects of the peroxidase systems on S. gordonii. Nonetheless, a number of other streptococcal species have been shown to be susceptible to inhibition by OSCN 2 in sufficient concentration, including Streptococcus oralis (van der Hoeven & Camp, 1993), Streptococcus mitior (Donoghue et al, 1987), Streptococcus rattus (Donoghue et al, 1987), Streptococcus uberis (Marshall et al, 1986), Streptococcus dysgalactiae (Mickelson & Brown, 1985), Streptococcus agalactiae (Mickelson, 1979) and Streptococcus pyogenes (Mickelson, 1966). Importantly, many factors determine susceptibility to inhibition by OSCN 2 , including pH, the flux of the peroxidase system (availability of H 2 O 2 ), cell thiol content, stored carbohydrate content, and the ability of the medium to quench OSCN 2 .…”
Section: Inhibition Of Oral Streptococci By Hypothiocyanitementioning
confidence: 99%
“…In contrast to the large number of studies of the effects of the LPO and related systems on S. mutans, there have been relatively few studies of the effect on S. sanguinis (formally sanguis) (Carlsson, 1980;Carlsson et al, 1983;Courtois et al, 1995;van der Hoeven & Camp, 1993), and we are not aware of any efforts to quantify the effects of the peroxidase systems on S. gordonii. Nonetheless, a number of other streptococcal species have been shown to be susceptible to inhibition by OSCN 2 in sufficient concentration, including Streptococcus oralis (van der Hoeven & Camp, 1993), Streptococcus mitior (Donoghue et al, 1987), Streptococcus rattus (Donoghue et al, 1987), Streptococcus uberis (Marshall et al, 1986), Streptococcus dysgalactiae (Mickelson & Brown, 1985), Streptococcus agalactiae (Mickelson, 1979) and Streptococcus pyogenes (Mickelson, 1966). Importantly, many factors determine susceptibility to inhibition by OSCN 2 , including pH, the flux of the peroxidase system (availability of H 2 O 2 ), cell thiol content, stored carbohydrate content, and the ability of the medium to quench OSCN 2 .…”
Section: Inhibition Of Oral Streptococci By Hypothiocyanitementioning
confidence: 99%
“…Oram & Reiter (1966) and Mickelson (1966) suggested that the LP system, by oxidizing the thiol groups of a number of enzymes, interfered with glycolysis in some streptococci. More recently, Aune et al (1977) have examined the binding of the thiocyanate anion to bovine serum albumin in the presence of the LP system and have found that this involved the thiol groups of the protein.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, reports studying the growth conditions of S. agalactiae have been rare in the literature (Mickelson, 1966(Mickelson, , 1976Bernheimer et al, 1979). Thus, rigorous investigation of the production of high amounts of extracellular products by group B streptococci or high bacterial densities exceeding A660 values of 2.5-3.0 have so far not been reported.…”
Section: Discussionmentioning
confidence: 99%